Дослідження у Києві по Ярославському пров., 1/3 у 2008 р. - Зоценко, В.М.; Тараненко, С.П.; Бітковський, В.О.; Чорновол, С.Є.; Івакін, В.Г. (Археологічні дослідження в Україні, 2010)
Results of excavations at Podil of Kyiv at 1/3, Yaroslavskyi Lane are presented. Several horizons of building, in particular of the Ancient Rus period, were studied. Complexes from the 11th to the 13th centuries are mainly described, among which the remains of multi-tier dwelling (object 1) stand out.